Assets for integrating task-sharing strategies for hypertension within HIV clinics: Stakeholder's perspectives using the PEN-3 cultural model. - Juliet Iwelunmor; Ifeoma Maureen Obionu; Gabriel Shedul; Ekanem Anyiekere; Daniel Henry; Angela Aifah; Chisom Obiezu-Umeh; Ucheoma Nwaozuru; Deborah Onakomaiya; Ashlin Rakhra; Shivani Mishra; Erinn M Hade; et al. (PLoS ONE)
Background Access to antiretroviral therapy has increased life expectancy and survival among people living with HIV (PLWH) in African countries like Nigeria. Unfortunately, non-communicable diseases such as cardiovascular diseases are on the rise as important drivers of morbidity and mortality rates among this group. The aim of this study was to explore the perspectives of key stakeholders in Nigeria on the integration of evidence-based task-sharing strategies for hypertension care (TASSH) within existing HIV clinics in Nigeria. Methods Stakeholders representing PLWH, patient advocates, health care professionals (i.e. community health nurses, physicians and chief medical officers), as well as policymakers, completed in-depth qualitative interviews. Stakeholders were asked to discuss facilitators and barriers likely to influence the integration of TASSH within HIV clinics in Akwa Ibom, Nigeria. The interviews were transcribed, keywords and phrases were coded using the PEN-3 cultural model as a guide. Framework thematic analysis guided by the PEN-3 cultural model was used to identify emergent themes. Results Twenty-four stakeholders participated in the interviews. Analysis of the transcribed data using the PEN-3 cultural model as a guide yielded three emergent themes as assets for the integration of TASSH in existing HIV clinics. The themes identified are: 1) extending continuity of care among PLWH; 2) empowering health care professionals and 3) enhancing existing workflow, staff motivation, and stakeholder advocacy to strengthen the capacity of HIV clinics to integrate TASSH. Conclusion These findings advance the field by providing key stakeholders with knowledge of assets within HIV clinics that can be harnessed to enhance the integration of TASSH for PLWH in Nigeria. Future studies should evaluate the effect of these assets on the implementation of TASSH within HIV clinics as well as their effect on patient-level outcomes over time.